A formação docente nos subprojetos química do programa institucional de bolsa de iniciação à docência - Garcia, Lucas Venício (2013)
This study is an analysis of documentary stamp as it investigates, through sampling, ten subprojects chemistry of the first edition (2007) Programa Institucional de Bolsa de iniciação à Docência - Pibid. This analysis aimed to determine the main concepts related to teacher training (technical rationality and practical rationality) that emerge from such documents. In this perspective, initially, it was necessary to carry out a detailed study on the scope and philosophy of the program in the wake Pibid national. Then it became expedient for achieving a deeper investigative reporting on the technical and practical rationalism, the bias of teacher training, since these two types of matrices epistemological rationales are adopted to carry out the following survey. From conceptions assimilated the light of the two kinds of rationalities study, an analysis was made of two subprojects chemistry Capes scholarship program in each region of Brazil, totaling ten documents. This analysis included the approaches advocated in the first edition of subprojects chemistry Pibid. It was also possible to correlate either explicitly sometimes implicitly, the philosophy adopted by the subprojects with the two types of rationales studied in this thesis. One of the most important contributions of this study is to help outline what assumptions related to teacher training in chemistry, the Federal Institutions of Higher Education of Brazil adopted to form their future educators. Thus, we can commensurate to the importance that the program has Pibid, in current time, for the training system of teachers in our country.